Formulation "Chitosan Solution" As preparations Alternative Dental Plaque Inhibiting Growth And Saliva (Trial By In Vivo) - Tri Wiyatini; Endah Aryati Eko Ningtyas; Aning Susilowati (Jurnal Riset Kesehatan, 2013)
One method to prevent caries prevalence is by breaking the chain of caries causes. Bacteria as an agent of caries decay can be diminished. Utilization of waste in nature is more valuable. Extraction of shell of squid and shrimp can be proceeded as Chitosan. Chitosan contain antibacterial agent based on many researches. Aim of this research to formulate mouth wash contain chitosan and its influences on plaque index and pH saliva after rinsing. Chitosan mouth wash formulation is by dissolving chitosan powder on aquadest and added chemical agent as flavour, coloring and solvent. Research subyek was 10 students, cross over rinsing with chitsan mouth wash and control mouth wash. Rinsing was done every day at morning and night after tooth brushing for 5 days. Plaque index and pH saliva measured first day before rinsing and last day. Subyek’s compliance was determined by volume of mouth wash rest in the bottle at last day research. Washing out time was five days before the next five days for another mouth wash. Research result shown significanly differences on plaque index and pH saliva before nd after rinsing with chitosan mouth wash (p≤ 0,05). Meanwhile there was no significanly differences after rinsing with control group. Raise of pH saliva after rinsing with chitosan mouth wash is higher compared to control grou.ntocaterial agent